2008
DOI: 10.1101/gad.461808
|View full text |Cite
|
Sign up to set email alerts
|

Trans-regulation of the expression of the transcription factor MtHAP2-1 by a uORF controls root nodule development

Abstract: MtHAP2-1 is a CCAAT-binding transcription factor from the model legume Medicago truncatula. We previously showed that MtHAP2-1 expression is regulated both spatially and temporally by microRNA169. Here we present a novel regulatory mechanism controlling MtHAP2-1 expression. Alternative splicing of an intron in the MtHAP2-1 5leader sequence (LS) becomes predominant during the development of root nodules, leading to the production of a small peptide, uORF1p. Our results indicate that binding of uORF1p to MtHAP2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 51 publications
3
89
0
8
Order By: Relevance
“…In the model legume Medicago truncatula, Mt-HAP2-1 is expressed in the root nodule meristematic zone and is essential for the differentiation of root nodule cells (Combier et al, 2006). Spatial and temporal expression of this gene (and NF-YA subunits in general across plant lineages) is controlled by microRNA 169 (miR169; Jones-Rhoades and Bartel, 2004) as well as a small peptide encoded by its own 59 leader sequence (Combier et al, 2008). In Arabidopsis, miR169 is also strongly downregulated in response to nitrogen starvation, and this is correlated with the concomitant induction of multiple NF-YA family members, changes that are at least correlated to nitrogen sensitivity through the analysis of transgenic plants overexpressing miR169 (Zhao et al, 2011).…”
Section: Nf-y Transcription Factors In Plantsmentioning
confidence: 99%
“…In the model legume Medicago truncatula, Mt-HAP2-1 is expressed in the root nodule meristematic zone and is essential for the differentiation of root nodule cells (Combier et al, 2006). Spatial and temporal expression of this gene (and NF-YA subunits in general across plant lineages) is controlled by microRNA 169 (miR169; Jones-Rhoades and Bartel, 2004) as well as a small peptide encoded by its own 59 leader sequence (Combier et al, 2008). In Arabidopsis, miR169 is also strongly downregulated in response to nitrogen starvation, and this is correlated with the concomitant induction of multiple NF-YA family members, changes that are at least correlated to nitrogen sensitivity through the analysis of transgenic plants overexpressing miR169 (Zhao et al, 2011).…”
Section: Nf-y Transcription Factors In Plantsmentioning
confidence: 99%
“…The best example comes from the Medicago truncatula MtHAP2 mRNA, which encodes a transcription factor of the CCAAT enhancer binding protein class. A uORF peptide encoded by the MtHAP2 mRNA binds to the 5' leader, which causes the subsequent degradation of its transcript in the meristematic zone of the Medicago nodule (Combier et al, 2006;Combier et al, 2008). It is debatable whether this case should even be regarded as an example for a trans-acting uORF peptide, since the peptide regulates its own mRNA.…”
Section: Uorfsmentioning
confidence: 99%
“…It is possible that Enod40 can be partially induced by a signaling pathway that is independent of RabA2, or, alternatively, it might be a consequence of incomplete silencing by RNAi. Enod40 plays a role in cell division in the cortex leading to the formation of the nodule primordium (Charon et al, 1997(Charon et al, , 1999, and it was shown that a functional CCAAT transcription factor is also required for normal nodule development (Combier et al, 2006(Combier et al, , 2008. Therefore, RabA2 is required at early steps after Nod factor perception prior to early signaling events and root hair deformation.…”
Section: Raba2 Is Required For Nod Factor-induced Expression Of Enodsmentioning
confidence: 99%